Short Communication: Plant diversity utilization and land cover composition in the Subak Jatiluwih, Bali, Indonesia - Sutomo Sutomo; Rajif Iryadi; I Dewa Putu Darma; I Putu Agus Hendra Wibawa; Ayyu Rahayu; Siti Fatimah Hanum; Syamsul Rizal; Ledya Novamizanti; Jangkung Raharjo (Society for Indonesian Biodiversity, 2021)
Abstract. Sutomo, Iryadi R, Darma ID, Wibawa IPAH, Rahayu A, Hanum SF, Rizal S, Novamizanti L, Raharjo J. 2021. Short Communication: Plant diversity utilization, and land cover composition in the Subak Jatiluwih, Bali, Indonesia. Biodiversitas 22: 1424-1432. Subak is water management or irrigation system for paddy fields in Bali Island and it has been assigned as a UNESCO’s World Heritage Site. At a landscape level, it comprises several components which are forests, terraced paddy landscape, rice fields, villages and temples. Subak in Jatiluwih Village, Tabanan Regency depicts an area characterized by its natural appearance in the form of a vast rice valley with a dike in stratum following its natural contours (frequent terraces). This paper aimed to explore plant diversity in various vegetations around Subak Jatiluwih as well as their usage in the daily living of the local community. We also explore the potential application of drone for classifying the landscape patterns of the Subak.Vegetation sampling to record plant diversity was done using purposive sampling, and drone or Unmanned Aerial Vehicle (UAV) was used to map the Subak Jatiluwih landscape. The potential usage of each species was obtained through interview with key respondents, and the level of usage of each species was analyzed using the BIV (Benefit Index Value). Tegalan area shows the highest number plant diversity in Subak Jatiluwih area. Furthermore, there are four species of plants that have the highest BIV namely: Cocos nucifera L., Psidium guajava L., Areca catechu L. and Musa × paradisiaca L.. Various plant uses by the locals include for animal feed, building, ceremony, craft, and food and medicinal purposes. The landscape in Subak Jatiluwih is dominated the vast valley of rice fields that has strata following its natural contours. These conditions provide opportunities to applied the conservation strategy based on cultural and custom values.